(6c-7d)-(3c+6cd)=

Simple and best practice solution for (6c-7d)-(3c+6cd)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6c-7d)-(3c+6cd)= equation:


Simplifying
(6c + -7d) + -1(3c + 6cd) = 0

Remove parenthesis around (6c + -7d)
6c + -7d + -1(3c + 6cd) = 0
6c + -7d + (3c * -1 + 6cd * -1) = 0
6c + -7d + (-3c + -6cd) = 0

Reorder the terms:
6c + -3c + -6cd + -7d = 0

Combine like terms: 6c + -3c = 3c
3c + -6cd + -7d = 0

Solving
3c + -6cd + -7d = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '7d' to each side of the equation.
3c + -6cd + -7d + 7d = 0 + 7d

Combine like terms: -7d + 7d = 0
3c + -6cd + 0 = 0 + 7d
3c + -6cd = 0 + 7d
Remove the zero:
3c + -6cd = 7d

Combine like terms: 7d + -7d = 0
3c + -6cd + -7d = 0

The solution to this equation could not be determined.

See similar equations:

| 2p^2=-4p+1 | | -4x+2=-6 | | 42x-12x^2=0 | | 5x+11=2(4x+7) | | 3s-(0.5s+7.2)=32.8 | | 40y-40=-40+40 | | M=j-k | | -7-(-3-2g)-10=0 | | 7-5x=27 | | b^4=48 | | 4x+4(x+9)=20 | | y^2-10y+2x+25=0 | | (5a^3+6a)+(-3a^2-5a)= | | 2m-14=6 | | 5(3x+7)-(4x-6)=12 | | 5k-13=2k+2 | | (4+3x+x^2)+(6-9x+x^2)= | | 4t+9=-9t-13 | | -3(1+w)+4w=8 | | -6x+36=28 | | 8-(2x-6)=22 | | 4+8y+9n-2y-2n-17= | | -p^2+8p+4= | | 4z+3(z+7)=-14 | | 2(x-2y-7z)= | | -4p^3+32p^2+16p= | | 2(9x-8)= | | 2(a+5)-a=-7 | | 3y+14=13 | | 5x(x-6)= | | 3a(a+2)= | | 4+2*n=10 |

Equations solver categories